Pengaruh Cash Ratio, Debt to Eguity Ratio dan Asset Growth terhadap Return On asset Pada perusahaan Sub Sektor Hotel, Restoran dan Parawisata yang terdaftar Di Bursa Efek Indonesia (BEI) - Desi Aramana (Asosiasi Dosen Akuntansi Indonesia, 2021)
Return On assets is a ratio that shows the company’s ability to generate profits from assets used. Return On assets is used to measure the effectiveness of a company in generating profits by utilizing the assets it has.In results of this study can be obtained from testing the data carried out on three independent variables, Namely cash ratio, debt to eguity ratio, and asset growth. While the dependent variable in this study is return on asset in hotel, restaurant and tourism sub-sector companies listed on the Indonesia stock exchange in 2016 – 2018. The population in the study were 25 hotel, restaurant and tourism companies. Data is collected by noting documents, and analyzed by multiple linier regression analysis. The results of this study indicate that, (1) there is an effect of cash ratio on ROA (return on assets), (2) there is an influuence of debt to eguity to ROA (return om assets), (3) there is an effect of negatif assets growth on ROA (return on assets) and (4) there is no efluence together (significant) cas ratio, debt to eguity ratio and assets growth to ROA (return on assets).